From Budget to Prosperity: Analyzing the Village Fund's Contribution to Rural Advancement in Indonesia - Rizaldi, Muhammad; Suman, Agus; Ekawaty, Marlina (Journal of Indonesian Applied Economics, 2024)
Purpose This research aims to assess the influence of Village Funds on rural development, as proxied by the Village Development Index, across 33 provinces in Indonesia from 2018 to 2022. Design/methodology/approach This research uses the Panel Data Regression Model to analyze the data. Findings This finding implies a positive impact of the Village Fund in driving rural development. In addition, other endogenous variables, such as the Human Development Index (HDI) and population size, also show a significant influence on rural development outcomes. These results highlight the multifaceted nature of rural development, not only financial resources but also human development and demographic factors play crucial roles. Research limitations/implications This study uses the Village Development Index to describe the condition of village development, Village Fund as an interest variable, Human development index, rural poor population, and total provincial population as control variables. Originality/value While there are studies that use Village Development Index (VDI) as a dependent variable to measure the influence of the Village Funds, they still have limitations in terms of their research scope, typically confined to a single district or city. This study will complement previous research by examining villages in all provinces of Indonesia.